Doplňky sportovní výživy v přípravě českých veslařů juniorské kategorie - Kubrycht, Libor (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2008)
Title: Sports supplements in the nutrition of Czech junior rowers. Purposes: To review the sports supplements use in the nutrition of Czech junior rowers. Methods: Analyses of current scientific knowledge concerning sports nutrition, rowing physiology and performance enhancement were performed. Structured interviews with ten participants of the World Rowing Junior Championship were carried out to assess the competitors' personal experience. Results: All Czech junior rowers use sports supplements. However, apart from the appropriate sports supplements, they also use supplements which are not recommended by sports dietitians for their uncertain effect on health. Top Czech junior rowers do neither have clear understanding of the physiological reasons for the supplement use nor they are able to objectively assess its impact on their performance. Key words: rowing, supplement, nutrition